MARKETING STRATEGY AND DEVELOPMENT OF EDUCATIONAL TOURISMZOOLOGY MUSEUM IN BOGOR - Ade Suryana; Sri Indrayanti (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
The existence of museums is very important because they have an important role in preserving cultural heritage, education, and developing public knowledge. Museums also function as a place to collect, care for, and exhibit historical objects and artifacts that have historical and cultural value. Museums are often considered uninteresting and boring by the public, so they are rarely visited. This is due to several factors, such as unattractive exhibition layouts, lack of interaction with collections, and lack of effective promotion. This research is aimed at answering the questions of how is Zoological Museum in Bogor  carries out the marketing strategies to increase the number of visitors and what aspects need to be improved. In this study, researchers carried out semi structured interview to 20 visitors consist of secondary school students, college students, employees and common society. Researchers also did nonparticipants observation and observed visitors’ activities when they were in the museum. Result of this study indicates that the results of this study indicate that of the 7P marketing mix related to the marketing strategy of the Bogor Zoological Museum, it turns out that 6 have been carried out well, but one aspect that needs to be considered is the product issue, how the Zoological Museum can make this museum something interesting to see and visit.